An Empirical Investigation of Procedural Effect for Tax Administration in Lagos and Osun States of Nigeria - Ulabor, Ehimen Abiodun; Popoola, Emmanuel Kolawole O.; Akande, Olumide Saheed; Adefulu, Adedapo Adewale (African Journal of Stability and Development (AJSD), 2022)
All resource-dependent countries have experienced catastrophic economic and political crises, leading inevitably to their inability to meet the delivery of basic needs and security to their citizens. Many have had to turn to taxation to meet the shortfall in revenue generation from natural resources. This paper discusses the concepts of Tax, Tax Administration, Development of Tax, Tax Imposition, Model of Tax Administration, Nigerian Tax Laws, Tax Regulations, Fiscal Issues and Tax Transaction in Nigeria. It attempts to discuss some theories that have helped us to have vivid understanding of the subject matter of discussion. These theories are: Social Contract Theory, Benefit/Utility Theory, Ability to Pay Theory, and Principle of Equal Distribution Theory. Using data collected from Lagos and Osun State, this study sought to understand what the effect of procedure for tax administration has on effective taxation in the states. It is concluded that if tax administration in the study areas is well executed, the development of basic infrastructures for the general good of the citizens will improve, and this in turn will make citizens to see the need to want to comply more with tax demands.